MRI Observation After Intralabyrinthine and Vestibular Schwannoma Resection and Cochlear Implantation - Sudhoff, Holger; Gehl, Hans B.; Scholtz, Lars U.; Todt, Ingo (Frontiers in Neurology, 2020)
Objective: MRI observation is part of the regular follow-up after vestibular schwannoma (VS) or intralabyrinthine schwannoma (ILS) resection. Because cochlear implantation (CI) after resection is part of the audiological rehabilitation process, the MRI behaviour of CI systems needs to be considered. In light of recent developments in MRI artefact positioning and pain prevention, this study evaluates reproducible MRI observations after tumour resection and CI surgery as part of follow-up. Methods: In a retrospective study, we evaluated 9 patients with a T1 KM, T2 sequence MRI observation and CBCT after ILS/VS resection and CI. In all but one case, a CI with a diametrically bipolar magnet and a receiver positioned 8-9 cm behind the external auditory canal was performed. Results: In all but one case, MRI observation allowed for a pain-free visual assessment of the intralabyrinthine and internal auditory canal (IAC) regions. In one case, a painful dislodgement of the receiver magnet occurred. Conclusion: MRI follow-up after ILS and VS resection and CI is reproducibly possible. Implant choice and positioning should be considered before implantation to allow for a pain-free visual assessment afterwards.